2010
DOI: 10.1016/j.ab.2010.08.008
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of azido-NAD+ to assess its potential as a two-dimensional infrared probe of enzyme dynamics

Abstract: Enzyme active site dynamics at femtosecond to picosecond time scales are of great biochemical importance, but remain relatively unexplored due to the lack of appropriate analytical methods. Two-dimensional infrared (2D IR) spectroscopy is one of the only methods that can examine chemical and biological motions at this time scale, but all the IR-probes used so far were specific to a few unique enzymes. The lack of IR-probes of broader specificity is a major limitation to further 2D IR studies of enzyme dynamics… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
35
0

Year Published

2011
2011
2014
2014

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 20 publications
(35 citation statements)
references
References 44 publications
0
35
0
Order By: Relevance
“…The assignment of Fermi resonance is in agreement with a previous literature study, 28 although 2D IR studies of N 3 CNdU are needed for confirmation. 27, 28, 4853 …”
Section: Resultsmentioning
confidence: 99%
“…The assignment of Fermi resonance is in agreement with a previous literature study, 28 although 2D IR studies of N 3 CNdU are needed for confirmation. 27, 28, 4853 …”
Section: Resultsmentioning
confidence: 99%
“…In addition, because azide will not mimic the TRS in other systems and only binds a limited number of enzymes, other probes would also offer access to the dynamics in other systems. To this end, we have prepared and characterized azido-labeled analogs of NAD + , azido-NAD + , 103,104 in which the amide group on the nicotinamide ring has been replaced with an azide, and picolyl azide adenine dinucleotide (PAAD + ) in which the amide group is replaced by an azide that is separated from the pyridinium ring by a methylene spacer. 105 Azido-NAD + is attractive because it is a smaller perturbation than is PAAD + , but PAAD + has a significantly stronger transition moment.…”
Section: Fdh – Combining the Kinetic And Spectroscopic Methodsmentioning
confidence: 99%
“…We have recently shown that an azido-derivatized analog of NAD + , azido-NAD + , has the potential to be a general probe to investigate the active site dynamics of NAD-dependent enzymes. 40 This analog exhibits binding and kinetic properties that are similar to native NAD + for a number of enzymes, suggesting that the analog binds to the enzyme with minimal perturbations to the active site structure. For azido-NAD + we have also studied its spectroscopic characteristics.…”
Section: Introductionmentioning
confidence: 93%